Author Correction: Global patterns in mangrove soil carbon stocks and losses. Issue 3 (March 2018) - Atwood, Trisha; Connolly, Rod; Almahasheer, Hanan; Carnell, Paul; Duarte, Carlos; Lewis, Carolyn; Irigoien, Xabier; Kelleway, Jeffrey; Lavery, Paul; Macreadie, Peter; Serrano, Oscar; Sanders, Christian; et al.
In the version of this Article originally published, the potential carbon loss from soils as a result of mangrove deforestation was incorrectly given as '2.0–75 Tg C yr–1 '; this should have read '2–8 Tg C yr–1 '. The corresponding emissions were incorrectly given as '~7.3–275 Tg of CO2 e'; this should have read '~7–29 Tg of CO2 e'. The corresponding percentage equivalent of these emissions compared with those from global terrestrial deforestation was incorrectly given as '0.2–6%'; this should have read '0.6–2.4%'. These errors have now been corrected in all versions of the Article.